New Issues in Bank Regulation (The Quaid-i-Azam Memorial Lecture) (The Pakistan Development Review, 2002)
Deregulation, technology, and financial innovation are transforming banking. Indeed, banking is no longer the business it was even a few decades ago. The way banking services are provided has changed dramatically, and in many countries they are even offered by institutions that are quite different from traditional banks. As the old institutional demarcations become increasingly irrelevant, increased competition from other intermediaries has led to a decline in traditional banking in which banks took deposits and made loans that stayed on their books to maturity. Banks thus have been moving rapidly into new areas of business. In this evolving financial environment, the international banking community and the Basel Committee on Banking Supervision of the Bank for International Settlements (BIS) are currently wrestling with pinning down an appropriate regulatory framework. The regulatory response to these changes has been a move away from the increasingly ineffective command-and-control regulations to greater reliance on assessing the internal risk-management systems, the supervision of banks, and more effective market discipline. In the language of the New Basel Accord, this represents a shift in emphasis away from capital-adequacy rules toward supervision and market discipline. This paper provides an overview of the profound and rapid changes brought about by technology and deregulation, and discusses the hurdles that will have to be negotiated for putting in place a suitable regulatory framework. On the one hand, inadequate resolution of these challenges will create the wrong incentives and lead to banking fragility. On the other hand, overregulation carries the danger that it will retard the development of national financial systems, hinder the best use of available domestic savings, prevent countries from accessing international capital, and ultimately lead to slower growth. Developed financial systems are being challenged by the shift in regulatory focus, and the definition and implementation of appropriate regulatory standards is encountering substantial difficulties. Finding the right balance between regulation, supervision, and reliance on market discipline is likely to be even more difficult in developing and transition countries.